Individual licensing models and the role of Internet platform providers - LIU, Kung-Chung (Institutional Knowledge at Singapore Management University, 2017)
Internet platform providers (IPPs) have the potential of reaching every online user of copyrighted works and of enhancing the licensing efficiency of copyrighted works. This chapter explores legal mechanisms to transform this potential into reality: an obligation on copyright holders to issue license to active IPPs, an obligation on passive IPPs to acquire license from collective management organizations (CMOs) and the oversight over IPPs. It then discusses the desirability of cooperation among IPPs and CMOs. It concludes by venturing to advocate an international agreement that would facilitate global licensing of copyrighted works.